Have workplace forums contributed to worker participation? Some management perceptions - R. Van Der Walt (South African Journal of Business Management, 2008)
The Labour Relations Act No. 66 of 1995 introduced workplace forums (WPFs) as a structure to promote employee participation in decision-making in the workplace. The study gathered the perceptions of management representatives regarding the reason(s) for the establishment, the process of establishment as well as the functioning of workplace forums in their respective organisations. The results indicate that contrary to popular belief management representatives understand that greater employee participation is the reason for the establishment of a workplace forum and that the establishment and functioning of workplace forums take place in accordance with the prescriptions of the Act. It is recommended that management create a climate in which more workplace forums can be established.
Keywords: 650